Effects of work requirements on welfare migration - Karin Edmark (Institute for Labour Market Policy Evaluation (IFAU), 2007)
This study tests for a migration response to the implementation of stricter rules for welfare benefit receipt, in the form of mandatory participation in activation programs for welfare recipients, in Stockholm town districts. The hypothesis is that welfare benefit prone individuals will choose to live in a town district that has no program if they dislike the loss of leisure due to program participation more than they value the contents of the program, and vice versa. The results give some indications of a negative effect of the program on the outmigration of welfare prone individuals. This is however not robust to changes in comparison group nor in the sample of town districts. The conclusion that can be drawn is that there are no indications that activation programs lead to outmigration of welfare prone individuals.
Keywords: H53; H70; I38; R23; 330; Welfare migration; welfare-to-work; difference-in-difference-in-differences; Internationale Wanderung; Sozialstaat; Sozialhilfe; Aktivierende Sozialhilfe; Stockholm; Schweden